Fertility, Female Labor Supply and Public Policy - Patricia Apps; Ray Rees (Institute for the Study of Labor (IZA), 2001)
Historically, in virtually all developed economies there seems to be clear evidence of an inverse relationship between female labor supply and fertility. However, particularly in the last decade or so, the relationship across countries has been positive: for example countries like Germany, Italy and Spain with the lowest fertility rates also have the lowest female participation rates. We accept the hypothesis that the reason for this lies in the combined effects of a country?s tax system and system of child support, and we have sought to clarify this theoretically, using an extended version of the Galor-Weil model. The results suggest that countries with individual rather than joint taxation, and which support families through improved availability of alternatives to domestic child care, rather than through direct child payments, are likely to have both higher female labor supply and higher fertility. These results are strengthened when we take account of the heterogeneity among households that undoubtedly exists.
Keywords: J13; J22; H31; H53; 330; Fertility; taxation; labor supply; Fruchtbarkeit; Arbeitsangebot; Frauen; Frauenerwerbstätigkeit; Familienleistungsausgleich; Theorie